The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17265/1934-7391/2015.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Resveratrol in Wine through a New Vinification Procedure

Abstract: Sulphur dioxide is used in the vinification process as an antimicrobial agent, but it is also considered as an important risk factor for liver diseases. Stilbenes have inhibitory effects on the growth of lactic acid bacteria strains isolated from wine. The authors investigated the viability of obtaining free-SO 2 resveratrol-enriched red wines. Substitution of sulfite (7 g/100kg) for resveratrol (150 mg/L and 300 mg/L) in the vinification process did not change the basic physical and chemical properties of win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The impact of polyphenols on the adsorption capacity of yeast autolysate, pectinase activity, and β -glucosidase activity during fermentation affects the levels of free phenols [ 27 ]. Pastor et al [ 15 ] found that different concentrations of resveratrol can promote the presence of other polyphenols in wine. Anaya et al [ 18 ] also revealed a similar pattern for catechins, although no reports are currently available on the impact of DMY on the content of phenolic compounds in wine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of polyphenols on the adsorption capacity of yeast autolysate, pectinase activity, and β -glucosidase activity during fermentation affects the levels of free phenols [ 27 ]. Pastor et al [ 15 ] found that different concentrations of resveratrol can promote the presence of other polyphenols in wine. Anaya et al [ 18 ] also revealed a similar pattern for catechins, although no reports are currently available on the impact of DMY on the content of phenolic compounds in wine.…”
Section: Resultsmentioning
confidence: 99%
“…Undoubtedly, the wine industry has also taken notice of this phenomenon. In the production of Cabernet Sauvignon wine, Pastor et al [15] employed resveratrol at concentrations of 150 and 300 mg/L in lieu of SO 2 . They discovered that the inclusion of resveratrol in Cabernet Sauvignon wine resulted in a more aesthetically pleasing color, without any discernible impact on its fundamental physical and chemical properties or sensory attributes.…”
Section: Introductionmentioning
confidence: 99%
“…We use 100% pure Malbec wine from Mendoza, Argentine, 2022 harvest. In a previous investigation, we demonstrated that wine enriched with resveratrol does not have signi cant differences in physical and organoleptic characteristics compared to conventional wine [47].…”
Section: Wine Enriched With Resveratrolmentioning
confidence: 87%
“…Sarcopenia in combination with excess body fat, known as sarcopenic obesity, is increasingly recognized as a major health problem in the aging population due to its association with an increased risk of cardiometabolic abnormalities [45][46][47][48].…”
Section: Body Compositionmentioning
confidence: 99%
“…In a pilot study investigating the addition of resveratrol instead of sulphur dioxide, an antioxidant, during wine production, Pastor et al (2015) reported that the addition of two different concentrations of resveratrol (150 mg/L and 300 mg/L) did not have any negative effect on the organoleptic and sensory properties of the products. Researchers have also suggested that the negative effects of sulphur dioxide on health can be prevented with the addition of resveratrol.…”
Section: The Use Of Resveratrol As a Functional Component In Foodsmentioning
confidence: 99%